Green Energy Advances 2019
DOI: 10.5772/intechopen.81817
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Energy Model for the Production of Biomass Briquettes Based on Rice Husks in Peruvian Low-Income Agricultural Areas

Abstract: An energy model focuses on the sustainability of environmental proposals that use clean biomass technology. In this case, briquette production seeks to generate socio-environmental development in agricultural areas contaminated by the burning of rice husks. However, this agricultural waste product has a large heating capacity and can be used as a raw material for briquette production, replacing conventional contaminant fuels such as firewood and reducing Peru's annual energy consumption by approximately 833,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…The results also compare well with the data reported [19] using elephant grass and spear grass samples. However, the result obtained for 50:50 and 80:20 are lower than those of 20.7 MJ/kg and 17.3 MJ/kg for the same composition reported in the literature [20]. It was also observed that the briquettes at 60:40 and 90:10 have higher calorific values when compared with those that have been widely reported which are in the range 17 to 21 MJ/kg for biomass materials.…”
Section: Calorific Valuecontrasting
confidence: 53%
See 1 more Smart Citation
“…The results also compare well with the data reported [19] using elephant grass and spear grass samples. However, the result obtained for 50:50 and 80:20 are lower than those of 20.7 MJ/kg and 17.3 MJ/kg for the same composition reported in the literature [20]. It was also observed that the briquettes at 60:40 and 90:10 have higher calorific values when compared with those that have been widely reported which are in the range 17 to 21 MJ/kg for biomass materials.…”
Section: Calorific Valuecontrasting
confidence: 53%
“…The measured density ranged from 1.5 g/cm 3 to 3.0 g/cm 3 and shows that CS is the densest, and in theory, ought to have the highest energy content. The RH density of 1.5 g/cm 3 is greater than that of 0.678 g/cm 3 reported in the literature [20]. On the other hand, RH and the briquettes prepared at 50:50 are the lowest and hence have low energy contents.…”
Section: Density Measurementsmentioning
confidence: 56%